Surveillance endoscopy is associated with improved outcomes of oesophageal adenocarcinoma detected in patients with Barrett's oesophagus. Issue 8 (26th August 2015) - El-Serag, Hashem B; Naik, Aanand D; Duan, Zhigang; Shakhatreh, Mohammad; Helm, Ashley; Pathak, Amita; Hinojosa-Lindsey, Marilyn; Hou, Jason; Nguyen, Theresa; Chen, John; Kramer, Jennifer R
Abstract : Background: The effectiveness of surveillance endoscopy in patients with Barrett's oesophagus (BE) for reducing oesophageal adenocarcinoma (EAC)-related mortality in patients with BE is unclear. Methods: This is a cohort study of patients with BE diagnosed in the National Veterans Affairs hospitals during 2004–2009 excluding those with conditions that affect overall survival. We identified those diagnosed with EAC after BE diagnosis through 2011 and conducted chart reviews to identify BE surveillance programme, and indication for EAC diagnosis, verify diagnosis, stage, therapy and cause of death. We examined the association between surveillance indication for EAC diagnosis with or without surveillance programme and EAC stage and treatment receipt in logistic regression models, and with time to death or cancer-related death using a Cox proportional hazards regression model. Results: Among 29 536 patients with BE, 424 patients developed EAC during a mean follow-up of 5.0 years. A total of 209 (49.3%) patients with EAC were in BE surveillance programme and were diagnosed as a result of surveillance endoscopy. These patients were more likely to be diagnosed at an early stage (stage 0 or 1: 74.7% vs 56.2, p<0.001), survived longer (median 3.2 vs 2.3 years; p<0.001) and have lower cancer-related mortality (34.0% vs 54.0%, p<0.0001) and had a trend to receive oesophagectomy (51.2% vs 42.3%; p=0.07) than 215 patients diagnosed by non-BE surveillance endoscopy (17.2% of whom were BE surveillance failure). BE surveillance endoscopy was associated with a decreased risk of cancer-related death (HR 0.47, 0.35 to 0.64), which was largely explained by the early stage of EAC at the time of diagnosis. Similarly, the adjusted mortality for patients with cancer in a prior surveillance programme for overall death was 0.63 (0.47 to 0.84) compared with patients with cancer not in a surveillance programme. Conclusions: Surveillance endoscopy among patients with BE is associated with significantly better EAC outcomes including cancer-related mortality compared with other non-surveillance endoscopy.